2022
DOI: 10.1002/pssb.202100632
|View full text |Cite
|
Sign up to set email alerts
|

Mössbauer Spectrometry of Model Binary Fe100−xCrx (1 ≤ x ≤ 50) Alloys

Abstract: Herein, several ways to evaluate Mössbauer spectra of model binary Fe100−xCrx alloys with chromium content varying in the range from 1 to 50 at% (x = 0.94, 2.2, 4.9, 10.4, 15.4, 22.1, and 52.9) are discussed. For low chromium concentrations (up to 15 at%), the method of binomial distribution of individual sextets is suitable. Depending upon the Cr content, the number of sextets used can be, however, as high as 20. The specific number of sextets is determined according to probabilities of individual atomic site… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 35 publications
2
10
0
Order By: Relevance
“…where β coefficient determines the change (decrease) with increasing chromium concentration in 1NN-2NN assuming the random distribution of atoms. Based on the results from the articles by Košovský et al [44] and Dubiel et al [45,46,51] (see Figure 8), the chromium concentration was calculated, which reaches 13.9(0)-14.3(7) at% Cr and is similar to the value determined by chemical analysis.…”
Section: Resultssupporting
confidence: 72%
See 4 more Smart Citations
“…where β coefficient determines the change (decrease) with increasing chromium concentration in 1NN-2NN assuming the random distribution of atoms. Based on the results from the articles by Košovský et al [44] and Dubiel et al [45,46,51] (see Figure 8), the chromium concentration was calculated, which reaches 13.9(0)-14.3(7) at% Cr and is similar to the value determined by chemical analysis.…”
Section: Resultssupporting
confidence: 72%
“…The estimation of chromium solubility limit in NS219 steel was determined using the saturation value of the hyperfine magnetic field (29.4 T). On the basis of previous studies, [44][45][46] it can be concluded that the dependence of the magnetic hyperfine field as a function of the impurity atom has a linear character (Equation ( 6)):…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations